Chemical Constituent from the Pods of Cassia glauca, Lam. - Rai, K.N.; Kaushalendra, Kumar; Singh, Janardan (Asian Journal of Chemistry, 2010)
The present paper deals with the isolation and structural elucidation of a new flavonol glycoside: 5,7-dihydroxy-4´-methyxoy flavonol-3-O-β-D-galactopyranoside along with chrysophenol, physcion, kaempferide and quercetin from the pods of Cassia glauca.